Unraveling Disillusionment: An Examination of Ernest Hemingway’s The Sun Also Rises - Ali, Muhammad Ilham; Wuntu, Ceisy Nita; Tatipang, Devilito Prasetyo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2024)
This research aims to analyze the disappointment felt by the characters in the novel using an objective approach with a qualitative descriptive method. In this method, the researcher collects data from the novel in the form of quotations in the novel by summarizing accurate data, such as facts in the story and character depictions that describe disappointment. After the data is analyzed, the discussion of this journal includes the characters in The Sun Also Rises and how they experience disappointment due to war and socio-political upheaval at that time. The results of this study show that the concept of disillusionment in The Sun Also Rises can be well understood, it is the researcher's finding that the expression of a deep sense of disillusionment that permeates the lives of the characters, stemming from the impact of World War I and the Lost Generation's search for meaning and purpose. The researchers also have uncovered the profound sense of disillusionment that pervades the characters' lives, stemming from the aftermath of World War I and the Lost Generation's search for meaning and purpose.